68Ga-DOTATATE PET/CT of Ectopic Cushing Syndrome Due to Appendicular Carcinoid. (November 2019) - Diwaker, Chakra; Shah, Ravi Kumar; Patil, Virendra; Jadhav, Swati; Lila, Anurag; Bandgar, Tushar; Shah, Nalini
Abstract : Abstract: Approximately 5% to 15% cases of endogenous Cushing syndrome are due to ectopic adrenocorticotrophic hormone (ACTH)–producing neuroendocrine tumors, which are commonly located in bronchopulmonary system, thymus, and gastrointestinal tract including pancreas. Although carcinoid tumors of the appendix are revealed in 0.3% of patients undergoing routine appendectomy, ACTH-secreting appendicular carcinoid is a rare entity. We present a case of a 22-year-old woman with ectopic ACTH-dependent Cushing syndrome due to an appendicular carcinoid, which was localized with the help of 68 Ga-DOTATATE PET/CT scan.